The Construction of Citizenship Through Musical Performance in Toronto’s Settlement Houses, 1930-1939 - Yerichuk, Deanna (MUSICultures, 2016)
Throughout the 1930s, Toronto’s social settlement houses hosted various musical performances by and for the immigrant and working-class residents of Toronto’s poorest neighbourhoods. Given their overarching project of civic betterment, the performances became sites not only to validate the social success of musical work, but also to enact musically notions of citizenship. Within the settlement music schools, benefit concerts and pupil recitals featured conservatory-style music performances, which articulated Western European Art Music to an Anglo-Celtic Protestant norm for citizenship. However, annual spring festivals shifted notions of citizenship somewhat by celebrating the various cultures of immigrants through music and dance.